The Effect of Scarcity-Based Promotion on Impulse Buying in TikTok Shop Live Streaming: A Stimulus, Organism, Response Perspective - Nazwa Ramadhani; Adnan Kasofi; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This research looks at how well scarcity promotions work in TikTok Shop live streams, using the Stimulus-Organism-Response (S-O-R) model. Limited-time and limited-quantity scarcity types are tested, with emotional excitement as the mediator, analyzed via SEM-PLS. The findings show that scarcity signals do not significantly impact emotional excitement or impulse buying, with no mediating effect despite positive path directions. The results suggest that promotional overload can weaken emotional and behavioral responses, serving as contextual limits for the S-O-R framework in mature live commerce platforms.